2010
DOI: 10.1158/1055-9965.epi-09-1273
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth, Preterm Birth, Neonatal Stress and Risk for CNS Tumors in Children: A Nordic Population- and Register-Based Case-Control Study

Abstract: Background: The peak incidence of central nervous system (CNS) tumors in childhood indicates that intrauterine or neonatal characteristics are potential risk factors or symptoms of early onset of disease.Methods: We conducted a registry-based case-control study nested in the childhood populations of Denmark, Finland, Sweden, and Norway on the association between indicators of fetal growth and neonatal stress and childhood CNS tumor risk diagnosed during the period . Each of the 3,443 cases was matched individu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 51 publications
6
64
3
1
Order By: Relevance
“…9 In our expanded data set, we found an increased risk for CNS tumors in children with birth weight .4500 g but no associations with SGA or LGA.…”
Section: Figures 1 and 2 Andmentioning
confidence: 56%
See 2 more Smart Citations
“…9 In our expanded data set, we found an increased risk for CNS tumors in children with birth weight .4500 g but no associations with SGA or LGA.…”
Section: Figures 1 and 2 Andmentioning
confidence: 56%
“…8,9 The strongest effect was observed in the youngest age groups and persisted up to age 10 years. We also found an increasing risk with increasing head circumference but only among children diagnosed within the first year of life (except for the Norwegian data).…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…Knowledge about the aetiology of central nervous system (CNS) tumours in children is sparse; however, several studies indicate that the pathogenic process of CNS tumours in children is initiated prenatally (Linet et al, 1996;Fear et al, 2001;Harder et al, 2008;Schmidt et al, 2010). Furthermore, a few studies indicate that exposure to infectious agents around the time of birth or in early childhood might modulate the risk for CNS tumours (Linet et al, 1996;Linos et al, 1998;Fear et al, 2001;McNally et al, 2002;Hoffman et al, 2007).…”
mentioning
confidence: 99%
“…The effect of birth size characteristics, such as birth weight, fetal growth, gestational age, and head circumference, on brain tumor risk has mainly been investigated among children (1)(2)(3)(4)(5)(6)(7)(8). Although previous studies have shown that children born with a high birth weight had an elevated risk of brain tumors (1)(2)(3)(4), others have found no association (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%